Human papillomavirus prevalence and type‐distribution in cervical glandular neoplasias: Results from a European multinational epidemiological study. Issue 12 (14th July 2015) - Holl, Katsiaryna; Nowakowski, Andrzej M.; Powell, Ned; McCluggage, W. Glenn; Pirog, Edyta C.; Collas De Souza, Sabrina; Tjalma, Wiebren A.; Rosenlund, Mats; Fiander, Alison; Castro Sánchez, Maria; Damaskou, Vasileia; Joura, Elmar A.; et al.
<x xml:space="preserve">Abstract</x> Cervical glandular neoplasias (CGN) present a challenge for cervical cancer prevention due to their complex histopathology and difficulties in detecting preinvasive stages with current screening practices. Reports of human papillomavirus (HPV) prevalence and type‐distribution in CGN vary, providing uncertain evidence to support prophylactic vaccination and HPV screening. This study [108288/108290] assessed HPV prevalence and type‐distribution in women diagnosed with cervical adenocarcinoma in situ (AIS, N = 49), adenosquamous carcinoma (ASC, N = 104), and various adenocarcinoma subtypes (ADC, N = 461) from 17 European countries, using centralised pathology review and sensitive HPV testing. The highest HPV‐positivity rates were observed in AIS (93.9%), ASC (85.6%), and usual‐type ADC (90.4%), with much lower rates in rarer ADC subtypes (clear‐cell: 27.6%; serous: 30.4%; endometrioid: 12.9%; gastric‐type: 0%). The most common HPV types were restricted to HPV16/18/45, accounting for 98.3% of all HPV‐positive ADC. There were variations in HPV prevalence and ADC type‐distribution by country. Age at diagnosis differed by ADC subtype, with usual‐type diagnosed in younger women (median: 43 years) compared to rarer subtypes (medians between 57 and 66 years). Moreover, HPV‐positive ADC cases were younger than HPV‐negative ADC. The six years difference in median age for women with AIS compared to those with usual‐type ADC suggests that cytological screening for AIS may be suboptimal. Since the great majority of CGN are HPV16/18/45‐positive, the incorporation of prophylactic vaccination and HPV testing in cervical cancer screening are important prevention strategies. Our results suggest that special attention should be given to certain rarer ADC subtypes as most appear to be unrelated to HPV.